UJI CEPAT TETRAZOLIUM DAN RADICLE EMERGENCE (RE) TERHADAP DAYA BERKECAMBAH PADA VARIETAS BENIH JAGUNG (Zea mays L) - Aprilidia Rumintang Rajagukguk; Khairunnisa Lubis; Revandy Iskandar Damanik (JURNAL GALUNG TROPIKA, 2022)
Fast and applicable seed quality testing methods are needed to support the availability of quality seeds that can be distributed. The Tetrazolium Rapid Test Method is a rapid test method that is currently being implemented in Seed Quality Testing Laboratories. Meanwhile, the Radicle Emergence/RE Rapid Test method is currently being developed to accelerate the supply of quality seeds. This research aims to determine a more precise, efficient, and efficient method. Accurate in predicting corn seed germination in the laboratory and field. This research was carried out in the laboratory using a completely randomized design and in the field using a one-factor randomized block design, namely varieties in the form of ten varieties of corn (Sukmaraga, Srikandi Ungu, Srikandi Kuning, Pulut Uri, Lamuru, Bisi 18, Bisi 2, P32, P35, and Betras 1). The results showed that the Tetrazolium Rapid Test and the RE Rapid Test had a very close correlation in estimating the value of Seed Germination in the Laboratory and the Field. Both methods can be used as Rapid Test methods in Seed Quality Testing laboratories. However, the RE Rapid Test is more economical and practical.